Results of non-medical switching from original infliximab to its Russian biosimilar in patients with ulcerative colitis - Maria I. Timanovskaia; Oleg V. Knyzev; Asfold I. Parfenov (Терапевтический архив)
Aim. To evaluate the efficacy and safety of the Russian biosimilar infliximab in patients with ulcerative colitis (UC).